2002
DOI: 10.1177/146045820200800202
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of medical digital libraries

Abstract: Evidenced-based medicine has increased the importance of quick accessibility to reputable, upto-date information. Web-accessible digital libraries (DLs) on the wards can address the demand for such information. The use and acceptability of these resources has, however, been lower than expected due to a poor understanding of the context of use. To appreciate the social and organizational impacts of ward-accessible DLs for clinicians, results of a study within a large Londonbased hospital are presented. In-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 14 publications
(18 reference statements)
0
40
0
Order By: Relevance
“…• Informed consent (Adams and Blandford, 2002;Adams, Blandford and Lunt, 2005) included observations of clinical encounters between doctors and patients, for whom privacy and confidentiality were paramount concerns. In this case, anonymisation of data, for both individuals and institutions as a whole, was imperative -both for protecting privacy and also to maintain individuals' and organisations' trust in the research procedure.…”
Section: Ethicsmentioning
confidence: 99%
“…• Informed consent (Adams and Blandford, 2002;Adams, Blandford and Lunt, 2005) included observations of clinical encounters between doctors and patients, for whom privacy and confidentiality were paramount concerns. In this case, anonymisation of data, for both individuals and institutions as a whole, was imperative -both for protecting privacy and also to maintain individuals' and organisations' trust in the research procedure.…”
Section: Ethicsmentioning
confidence: 99%
“…One of the previous studies found that the availability and cost of searching Medline may have influenced its response rate across different hospitals ) and more recent research has suggested that despite the obvious improvement in accessibility of digital libraries and web resources there are social contexts in which these tools are used which may still constrain their accessibility (Adams & Blandford 2002;Urquhart et al 2001).…”
Section: Research Contextmentioning
confidence: 99%
“…Adams and Blandford, 2002). As with different kinds of models, attention paid at different levels yields different insights into the qualities of interactions between users and devices and makes it possible to answer different kinds of questions.…”
Section: Levels Of Descriptionmentioning
confidence: 99%